What affects acceptance of Urban Air Mobility services? - Almeida, H.; Kalakou, S.; Ferreira, T. (EWGT2025: EURO Working Group on Transportation Conference 2025, 2025)
Unmanned aerial vehicles (UAVs) are expected to provide mobility services for passengers soon. The work presented in this study deals with the topic of Urban Air Mobility (UAM) acceptance. A survey was designed to capture information on UAM perceptions on acceptance, adoption categories, mobility behaviour, and socioeconomic aspects. It employs Rogers' (2003) technology diffusion theory, categorizing respondents into innovators, early adopters, early majority, late majority, and laggards. The survey was pilot tested and distributed through email and social media, resulting in 391 valid responses from Lisbon residents. A linear regression model was developed using 80% of the sample for calibration and 20% for validation. Five dimensions were designated and found to affect UAM acceptance: transport social benefits, transport personal benefits, UAM safety concerns, UAM pollution aspects and environmental consciousness. The model accounted for 56% of the dependent variable's variance and was statistically significant. The validation results confirmed the model's reliability. Understanding citizen perceptions is crucial for UAM integration in urban transport systems, the findings highlight the importance of considering personal and social benefits, environmental consciousness, safety concerns, and urban planning in UAM adoption strategies. The study provides insights for industry stakeholders, policymakers, and mobility operators to design UAM services that meet public acceptance.